2023
DOI: 10.1113/ep091054
|View full text |Cite
|
Sign up to set email alerts
|

High preoperative bradykinin level is a risk factor for severe postoperative hypoxaemia in acute aortic dissection surgery

Abstract: New Findings What is the central question of this study?Hypoxaemia can lead to increased postoperative mortality in patients: what are the independent risk factors for severe hypoxaemia after acute Stanford type A aortic dissection? What is the main finding and its importance?Severe postoperative hypoxaemia was found in 36.4% of patients, and it was determined that high preoperative bradykinin levels and increased BMI were independent predictors of severe postoperative hypoxaemia in patients with acute Stanfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…We previously found that bradykinin is a risk factor for severe hypoxemia after surgery with HCA, 20 suggesting that bradykinin might act as an endogenous pathogenic factor. We explored the relationship between bradykinin and the HCA process and postoperative AKI.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that bradykinin is a risk factor for severe hypoxemia after surgery with HCA, 20 suggesting that bradykinin might act as an endogenous pathogenic factor. We explored the relationship between bradykinin and the HCA process and postoperative AKI.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it's pivotal to recognize that the prognostic implications of UHS can be heterogeneous, contingent upon individualized patient parameters. For instance, the obese subset might still grapple with an accentuated risk of postoperative hypoxemia, attributed to factors such as diminished pulmonary volume and heightened respiratory workload ( 10 ). Thus, exploring TAR outcomes via UHS across varying body mass index (BMI) strata is paramount, intending to refine surgical methodologies through the adoption of minimally invasive paradigms.…”
Section: Introductionmentioning
confidence: 99%